Alternative capitalisms : geographies of emerging regions - Gwynne, Robert N. (Arnold ; Distributed in the United States of America by Oxford University Press, 2003)
This unique book aims to examine the effects of globalization and economic and political transformations in those parts of the world which are now regularly referred to as 'emerging regions'.